Strengthening Transparency in the Oil Sector in Cameroon : Why Does it Matter? - Cosse, Stephane (Washington, D.C. : International Monetary Fund, 2006)
There has been a growing recognition of the importance of transparency for economic growth and social development in oil producing countries. This paper analyzes transparency issues in Cameroon's oil sector. It shows that, while substantial efforts have already been undertaken, continued action is necessary to strengthen transparency. The paper seeks to identify why and how transparency, especially in the fiscal area, matters for economic development and poverty reduction in Cameroon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet